Impact and mitigation of blade surface roughness effects on wind turbine performance - Kelly, J; Vogel, C; Willden, R (Wiley, 2021)
This paper presents a numerical study of the effects of blade roughness on wind turbine performance and annual energy production and how these effects may be partially mitigated through improved control. Three rotors are designed using the NACA4415, S801 and S810 airfoils, and blade element momentum theory is used to model wind turbine behaviour. The aerodynamic lift and drag data for the clean and roughened airfoils are taken from previous experimental work. These show that surface roughness leads to a decreased airfoil lift coefficient and an increased drag coefficient across an angle of attack range typical for large wind turbines, which will clearly lead to decreased turbine performance. Three separate control methods are considered for wind turbines with roughened blades operating at each of four candidate wind sites with different wind speed distributions. Results show that, compared to clean rotor blades, the roughened blades lead to a performance drop in the range of 2.9–8.6% for a torque based control strategy. A control-based performance recovery strategy, in which the controller gain coefficient is re-optimised, increased roughened rotor annual energy production by 0.1–1.0%.